алгебра 7 класс

Номер 873

Условие:

Упростите выражение:
а) (х - 2)(х + 2) - х( х + 5);
б) m(m - 4) + (3 - m)(3 + m);
в) (4x - а)(4х + а) + 2х(х - а);
г) 2а(а + b) - (2а + b)(2а - b);
д) (5а - 3с)(5а + 3с) - (7с - а) (7с + а);
е) (4b + 10с)(10с - 4b) + (-5с + 2b)(5с + 2b);
ж) (3х - 4у)2 - (3x - 4у)(3х + 4y);
з) (2а + 6b)(6b - 2а) - (2а + 6b)2.

 

Ответ:

а) (х - 2)(х + 2) - х • ( х + 5) = x2 - 4 - x2 - 5x = -4 - 5х;
б) m • (m - 4) + (3 - m)(3 + m) = m2 - 4m + 9 - m2 = 9 - 4m;
в) (4x - а)(4х + а) + 2х • (х - а) = 16x2 - a2 + 2x2 - 2xa = 18x2 - a2 - 2xa;
г) 2а • (а + b) - (2а + b)(2а - b) = 2a2 + 2ab - 4a2 + b2 = -2a2 + 2ab + b2;
д) (5а - 3с)(5а + 3с) - (7с - а)(7с + а) = 25a2 - 9c2 - 49c2 + a2 = 26a2 - 58c2;
е) (4b + 10с)(10с - 4b) + (-5с + 2b)(5с + 2b) = 100c2 - 16b2 + 4b2 - 25c2 = 75c2 -12b2;
ж) (3х - 4у)2 - (3x - 4у)(3х + 4y) = 9x2 - 24xy + 16y2 - 9x2 + 16y2 = 32y2 - 24xy;
з) (2а + 6b)(6b - 2а) - (2а + 6b)x2 = 36b2 - 4a2 - 4a2 - 36b2 - 24ab = -8a2 - 24ab.